D/H isotope ratios in the global hydrologic cycle. Issue 12 (18th June 2015) - Good, Stephen P.; Noone, David; Kurita, Naoyuki; Benetti, Marion; Bowen, Gabriel J.
Abstract Deuterium to hydrogen (D/H) ratios in Earth's hydrologic cycle have long served as important tracers of climate processes, yet the global HDO budget remains poorly constrained because of uncertainties in the isotopic compositions of continental evapotranspiration and runoff. Here bias‐corrected satellite retrievals of HDO and H2O concentrations from the Tropospheric Emissions Spectrometer are used to estimate the marine atmospheric surface layer HDO vapor pressure deficit, from which we calculate the global flux‐weighted average oceanic evaporation isotopic composition as −37.6‰. Using these estimates, combined with D/H ratios in precipitation, global mass balance suggests H isotope compositions for global runoff and terrestrial evapotranspiration of −77.3‰ and −40.0‰, respectively. By resolving the HDO budget, we establish an accurate global baseline for geochemically enabled Earth system models, demonstrate patterns in entrainment of moisture into the marine surface layer, and determine the isotopic composition of continental fluxes critical for global ecohydrologic investigations.